2019
DOI: 10.1080/00224499.2019.1644485
|View full text |Cite
|
Sign up to set email alerts
|

“This Is Me, This Is What I Am, I Am a Man”: The Masculinities of Men Who Pay for Sex with Women

Abstract: This paper draws on theories of masculinity to explore men's motivations for beginning and continuing to pay for sex with women. Based on in-depth interviews with thirty-five male clients of female sex workers in the UK during 2007/2008, our findings suggest that a desire to pay for sex is often entrenched in notions of hegemonic masculinity (Connell, 2000) such as sex as a drive, or need for a variety of experiences and partners and is rationalised as an economic exchange. Yet, the men interviewed also expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 107 publications
(104 reference statements)
2
25
0
Order By: Relevance
“…A recent systematic review of the qualitative literature about MWPWS suggests that their diverse experiences are at once gendered, sexual, intimate, consumerist, and related to power relations, and social stigma (Prior & Peled, submitted for publication B). Thus, for example, studies show that SFP enables MWPWS to fulfill their sexual desires (Huysamen, 2019), and boost their sense of masculinity (Hammond & van Hooff, 2019;Lahav-Raz, 2019a). However, other studies have found that MWPWS may also experience a sense of compromised sexual potency and flawed masculinity when paying for sex (Prior & Peled, 2019).…”
Section: The Experiences Of Mwpwsmentioning
confidence: 99%
“…A recent systematic review of the qualitative literature about MWPWS suggests that their diverse experiences are at once gendered, sexual, intimate, consumerist, and related to power relations, and social stigma (Prior & Peled, submitted for publication B). Thus, for example, studies show that SFP enables MWPWS to fulfill their sexual desires (Huysamen, 2019), and boost their sense of masculinity (Hammond & van Hooff, 2019;Lahav-Raz, 2019a). However, other studies have found that MWPWS may also experience a sense of compromised sexual potency and flawed masculinity when paying for sex (Prior & Peled, 2019).…”
Section: The Experiences Of Mwpwsmentioning
confidence: 99%
“…Birch 2015; Huysamen 2019; Kong 2015Kong , 2016McKeganey and Barnard 1996;Monto 2010). The motivation to purchase (or sell) sex can be understood in terms of push and pull factors and paying for sex involves a complex range of motivations beyond sexual pleasure and relief (Hammond and van Hooff 2020;Sanders 2008b;Vanwesenbeeck 2013). In a study on men who purchase sex, differences were identified between one-time visitors and regulars in the motivations for purchasing sex and in the dynamics of the commercial relationship (Sanders 2008a).…”
Section: The Purchase Of Sex and Intimacymentioning
confidence: 99%
“…Sanders, Brents, and Wakefield 2020). Practices such as the purchase of sex, are often associated with unequal power relations (see Hammond and van Hooff 2020), and combining sex and money is commonly considered problematic and morally objectionable (Rubin 1998;SOU 2010, 49). The political and legal approach to commercial sex has been handled differently in different national contexts (Sanders, Brents, and Wakefield 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A man may start a relationship with a sex worker as a client through a casual encounter intended to meet sexual desires, and then develop a long-term relationship (Hammond and van Hooff 2020). Such relationships are challenging for both the woman and the man, as they attempt to define their relationship differently from that of the woman's encounters with clients (Bhattacharjee et al 2018;Warr and Pyett 1999;Mbonye et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hegemonic masculinity has been implicated in men's pursuit of paid sex (Hammond and van Hooff 2020;Shumka, Strega, and Hallgrimsdottir 2017). When clients become lovers they cannot expect to have a monopoly over sex with a woman, something that may be challenging to dominant forms of masculine identity (Huynh et al 2019;Jewkes et al 2012).…”
Section: Introductionmentioning
confidence: 99%